HIV treatment as prevention: issues in economic evaluation - Bärnighausen, Till; Salomon, Joshua A.; Sangrujee, Nalinee (PLoS medicine, 2012)
Meyer-Rath and Over assert in another article in the July 2012 PLoS Medicine Collection, “Investigating the Impact of Treatment on New HIV Infections”, that economic evaluations of antiretroviral therapy (ART) in currently existing programs and in HIV treatment as prevention (TasP) programs should use cost functions that capture cost dependence on a number of factors, such as scale and scope of delivery, health states, ART regimens, health workers' experience, patients' time on treatment, and the distribution of delivery across public and private sectors. We argue that for particular evaluation purposes (e.g., to establish the social value of TasP) and from particular perspectives (e.g., national health policy makers) less detailed cost functions may be sufficient. We then extend the discussion of economic evaluation of TasP, describing why ART outcomes and costs assessed in currently existing programs are unlikely to be generalizable to TasP programs for several fundamental reasons. First, to achieve frequent, widespread HIV testing and high uptake of ART immediately following an HIV diagnosis, TasP programs will require components that are not present in current ART programs and whose costs are not included in current estimates. Second, the early initiation of ART under TasP will change not only patients' disease courses and treatment experiences—which can affect behaviors that determine clinical treatment success, such as ART adherence and retention—but also quality of life and economic outcomes for HIV-infected individuals. Third, the preventive effects of TasP are likely to alter the composition of the HIV-infected population over time, changing its biological and behavioral characteristics and leading to different costs and outcomes for ART.